DEVELOPING A COLLABORATIVE TEACHING SYNTAX FOR EFFECTIVE ONLINE LEARNING TRANSITIONS - Pujianto, Pujianto; Perdana, Riki; Setiaji, Bayu; Wibowo, Muhammad Wahyu; Laily, Rana; Sasauw, Dinda Permata (Jurnal Pendidikan Fisika, 2024)
The transition of learning using an online platform where there is a lack of preparation of educators in the transition of online learning and there are challenges to meet the needs of online learning. Therefore, the right strategy is needed to help educators to improve learning in the classroom. This research is research and development type Research and Development (RD). This development research aims to produce a product in the form of a collaborative teaching learning model syntax. Researchers develop learning media using the 4D development model. The 4D model is a model consisting of: define, design, develop and disseminate. The syntax development of the collaborative teaching learning model that was developed was tested by 7 validators consisting of 4 physics education lecturers at Universitas Negeri Yogyakarta and 3 high school (SMA) teachers. Based on data from validation results by validators on learning media, a score for each aspect was obtained, namely 3.36; 3.43; 3.57; 3.33; 3.33; 3.29; 3.14; 3.43 with an average score of 3.36 in the very valid category. Therefore, the syntax of the learning model developed meets the criteria for being very valid and can be used in learning..